Effect of regulated deficit irrigation on fatty acids and their derived volatiles in 'Cabernet Sauvignon' grapes and wines of Ningxia, China. (15th April 2018) - Ju, Yan-lun; Liu, Min; Tu, Ting-yao; Zhao, Xian-fang; Yue, Xiao-feng; Zhang, Jun-xiang; Fang, Yu-lin; Meng, Jiang-fei
Highlights: Irrigation with 60% evapotranspiration (ETc) increase the content of unsaturated fatty acids in grape berries. Irrigation with 60% ETc treatment decrease the level of alcohols and esters volatiles in wines. Irrigation with 70% and 80% ETc treatments enhance C6 volatiles in wines. The accumulation of C6 compounds is closely related to UFAs, especially linolenic acid and linoleic acid. Abstract: The effect of regulated deficit irrigation (RDI) on fatty acids and their derived volatiles in 'Cabernet Sauvignon' grapes and wines was investigated during two growing seasons in the east foot of Mt. Helan, the semi-arid area. The vines received water with 60% (RDI-1), 70% (RDI-2), 80% (RDI-3), 100% (CK, traditional drip irrigation) of their estimated evapotranspiration (ETc) respectively. RDI treatments resulted in lower yield, berry weight and titratable acidity with higher total soluble solids. RDI-1 increased the content of unsaturated fatty acids in berries and decreased the level of alcohols and esters volatiles in wines. RDI-2 and RDI-3 enhanced 1-hexanol and esters in wines in comparison with CK. The concentrations of C6 aroma compounds were closely correlated with unsaturated fatty acids ( p < .05), especially linolenic acid and linoleic acid. The present results provided direct evidence and detailed data to explain the effect of RDI on grapes and wines composition regarding fatty acids and their derived volatiles.